Penguatan Nilai Toleransi Mahasiswa Melalui Kegiatan Modul Nusantara Program Pertukaran Mahasiswa Merdeka - Kusuma Anggara; Erna Yuliandari; Moh. Muchtarom (Jurusan Ilmu Sosial Politik, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2023)
The aim of this article is to elucidate a strategy for enhancing students' tolerance values through the implementation of the Nusantara Module activities as part of the Free Student Exchange Program at Muhammadiyah University of Makassar. This study employs a qualitative methodology, with data obtained from a range of sources, including informants, locations, events, and documents. Purposive sampling is employed as the sampling technique, with data collection techniques involving interviews, document analysis, and observation. The validity test technique utilized in this study comprises data source triangulation and method triangulation. The findings of this study demonstrate that the strategy to strengthen student tolerance values can be accomplished through a range of activities, including diversity, inspiration, reflection, and social contribution. These activities demonstrate that the Nusantara module activities leverage a value classification approach and a value analysis approach in their efforts to enhance students' tolerance values. The primary limitation of this study is its inability to assess online activities that may have been conducted.